ACHIEVEMENT OF BLOOD PRESSURE TARGET WITH MEDICATION ADHERENCE AND SODIUM CONSUMPTION IN SAIFUL ANWAR GENERAL HOSPITAL OUTPATIENT CLINIC - Zaky Soewandi Ahmad; Dudella Desnani Firman Yasin (UPT Penerbitan Universitas Jember)
Hypertension is a common clinical problemthat responsible of deaths account for 9.4 millionpeople in worldwide every year.1 The worldwideprevalence of hypertension estimated increase from26.4% in 2000 to 29.2% in 2025.2 An estimated 65million adult Americans, or nearly one fourth of theadult population of the United States, havehypertension. Another quarter of the populationhave prehypertension.3 RISKESDAS results showsthat the prevalence of hypertension in Indonesia was26,5%.4Among hypertensive patients in USA 11%were not on treatment regimen, 25% were not onadequate treatment, 34% were on adequatetreatment.3 In Indonesia, among hypertensivepatients only 9,5% were on treatment.4 In a recentanalysis of National Health and NutritionExamination Survey (NHANES) participants that 35,8million (53,5%) were not reach blood pressuretarget. Among these, an estimated 16.0 million(44.8%) were aware of their hypertension and werebeing treated with medication.5 In a cross-sectionalanalysis of Framingham Heart Study participants,only 48% of treated participants were controlled to<140/90 mm Hg and less than 40% of elderlyparticipants (>75 years of age) were at a goal bloodpressure.6 These data suggested that hypertensionremained largely uncontrolled worlwide.Uncontrolled hypertensive confer an increased ofcardiovascular events. Nearly one fourth of adultswith uncontrolled hypertension have stage 2hypertension (systolic BP ≥160 mmHg or a diastolicBP ≥100 mmHg), putting them at higher risk forheart disease or stroke.5 According to the WorldHealth Report uncontrolled hypertension causesover 7 million premature deaths, takes up 4.5% ofthe total global disease burden, and accounts forsome 64 million disability adjusted life years lost.7Randomized controlled trials haveconvincingly shown that treatment of hypertensionreduces the risk of stroke, coronary heart disease,congestive heart failure, and mortality.8 However itwas not easy to achieve blood pressure target. Itrequired an act of antihypertensive medicationtherapy. The success of a therapy was not onlydetermined by the diagnosis and appropriate drugselection, but also to carry out the patient's therapycompliance, included compliance in takingmedication but in fact, adherent of medication waspoor.9 Moreover, non pharmacology theraphy thattreated hypertension is dietary of sodium. Reducingdietary sodium additives may decrease hypertensionprevalence by 30%, resulting in one million fewerhypertensive patients.10 It remains lacking dataregarding controlled hypertension in Indonesia up tonow. Therefore this research aimed to to investigatemedication adherence and sodium consumption toachieve blood pressure target.